Effectiveness of the Workshop “Adolescent Depression: What Can Schools Do?” - Martínez, Vania; Espinosa, Daniel; Zitko, Pedro; Marín, Rigoberto; Schilling, Sara; Schwerter, Camila; Rojas, Graciela (Frontiers in Psychiatry, 2015)
Introduction: Adolescent depression is associated with serious consequences. School staff is in a unique position to screen and refer adolescents with depression in a timely manner, and can collaborate with healthcare teams to assist in the proper management of the disease. The objective of this paper is to describe the results of a workshop that aims to improve the knowledge of adolescent depression among school staff. Material and methods: This was a single-arm trial with a pre-post design. Six workshops were conducted in four cities in Chile. Each workshop lasted four hours. Participatory methodology was used. A 26-item knowledge questionnaire about adolescent depression, with the alternatives “I agree”, “I disagree”, and “I don’t know” was administered to the participants, before and after the workshop. Results: A total of 152 people participated in the trial. Of these, 74.3% were female, and 44.7% were school psychologists, 25.0%, teachers, 17.8%, school counselors, and 5.3%, social workers. On average, there were 69.6% (SD 21.3) correct responses on the initial test, and 91.8% (SD 8.0) on the final test. All items had an increase of correct answers and a decrease of “don’t know” answers. There were notable increases of correct responses on statements dealing with myths: “Antidepressants for the treatment of depression in adolescents must be avoided because they produce dependence” (59% to 96%) and “Depression in adolescence is better defined as a weakness of character than as a disease” (75% to 95%). School psychologists scored higher than the other participants on the questionnaire both before and after the workshop. Conclusions: The workshop: “Adolescent depression: What can schools do?” can improve school staff knowledge of this topic, especially aiding to dispel myths regarding the disease and its treatment. This can help bring about timely case detection and improved collaboration with health team for proper handling of adolescent depression.